From Intermarium to the Three Seas Initiative - Regional Integrations in Central and Eastern Europe and the Hungarian Foreign Policy (Politeja, 2017)
From Intermarium to the Three Seas Initiative - Regional Integrations in Central and Eastern Europe and the Hungarian Foreign PolicyThe aim of the paper is to examine the harmony between the Polish and the Hungarian foreign policy from the early 20th century to the recent decades. Due to their special geographical position both states experienced threats and challenges in the examined period, however their approach to the above was different. Poland was focusing on the problem of the rebirth of the divided state and the uncertainty regarding its borders while Hungary had to struggle with the peaceful revision of the lost territories. Being located between two ambitious great powers Poland and Hungary had to find balance between German and Russian (Soviet) aspirations that influenced the foreign policy of both states. This paper treats Poland as a reference point and examines the Hungarian struggles from this approach. The paper also gives an outline definition of the meaning of borders and their importance in Central and Eastern European region.